The Challenges of Internationalization for Lithuanian Higher Education - Želvys, Rimantas (Acta Paedagogica Vilnensia, 2006)
Internationalization is one of the inevitable consequences of globalization, and internationalization of higher education is especially noticeable during the recent decades. An international market of higher education services is rapidly developing throughout the world. E.g., Van der Wende (2003) writes that in a number of countries (e. g. US, Australia, UK) governments have identified higher education export as a promising economic activity and important source of additional income. However, higher education researchers fear that transnational education could be detrimental to smaller nations and languages. In particular, Andere (2004) warns that governments of less developed countries should not intervene in the international higher education market, because by promoting exchanges and international education, they use very costly and scarce resources. The differences are evident even when one compares the relatively prosperous European countries. Van der Wende (2003) points out that currently the main importers of transnational education in Europe are Greece, Italy and Spain, and the main exporters are UK and US. So far Lithuania is mainly the importer of transnational education, and it inevitably leads to a number of financial as well as social implication. The deeper insight into the processes of internationalization could lead to a development of a more effective national higher education policy.
Keywords: internationalization; globalization; higher education policy